Four heat shock proteins of Drosophila melanogaster coded within a 12-kilobase region in chromosome subdivision 67B. - Corces, V.; Holmgren, R.; Freund, R.; Morimoto, R.; Meselson, M. (Proceedings of the National Academy of Sciences of the United States of America, 1980)
Unique coding sequences for four heat shock proteins of Drosophila melanogaster, hsp 28, hsp 26, hsp 23, and hsp 22, are clustered in a 12-kilobase interval at chromosome subdivision 67B. The four genes are not transcribed in the same direction and each gives rise to a separate messenger RNA, with no indication of intervening sequences. Including the present results, the genes for all seven major heat shock proteins of D. melanogaster are now cloned are found to exhibit a variety of patterns of organization at the five loci they occupy.